Designing User Experience Mobility Assistant Application for the Physically-Disabled Using the Wheel Method - Azman Fatahillah; Auzi Asfarian (Department of Informatics, Universitas Muhammadiyah Surakarta, Indonesia, 2020)
This research was conducted to design a mobility assistant application for persons with physical disability using The Wheel method. This application can assist mobile activities for people with disability. The application called Kuygo was made in four stages: analysis, design, prototype, and evaluation. Analysis of user needs is carried out at Loka Bina Karya (LBK) Bogor through observation and interviews. The interaction design requirements are generated in the form of requirements statements and inventory tasks with three main tasks, namely mobility preparation, mobility comfort, and providing a review of a location. Afterwards, discussions were held in the form of design thinking and ideation sessions, with people who care about people with disabilities and the Senyum Difabel community, which produced sketches, storyboards, and wireframes. Furthermore, the design implementation is carried out by making a prototype of medium-fidelity and the results are tested using cognitive walkthrough techniques. Of the four questions that must be answered with cognitive walkthrough techniques, the average success rate of all the tasks tested is 94.62%. Based on these results, no major usability errors were found in the prototype medium-fidelity and the Kuygo application can be further developed.